Analysis of vegetation types and floristic similarity in the Parque do Rio Doce, Minas Gerais - Padoan, Lucas de Lima Fernandes; Souza, Leonardo Vasconcelos de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The objective of this study is to analyze the plant formations observed in the Parque do Rio Doce – PERD. It is important to highlight the remarkable biodiversity in the region, serving, such as the basis for research and monitoring of aquatic fauna. Also it is interesting to highlight a wealth and diversity of flora, since it refers to one of the largest green areas preserved in a vegetation type of the Atlantic Forest. Because of such wealth, the Park has a herbarium that allows the study and identification of local species. Thus, we analyze here the vegetation types and apply a statistical methodology to measure the floristic similarity in different vegetation types present in the park. Configure the data produced here in an attempt to establish an overview of vegetative stratification of the region in question, providing, in such a way, a database that can assist new comparative studies. Finally, we emphasize the importance of protected areas in the broader context of environmental conservation in Brazilian territory, since we are in a pessimistic scenario areas, leaving only small islands of vegetation, which, in other words, just defending ourselves from ourselves.